Efforts to Improve Teacher Performance Through Academic Supervision of Madrasah Principals - Asmah Amir; Sitti Asmah; Andi Hajar (Eduvest - Journal of Universal Studies, 2022)
The goal to be achieved from the results of this study is to describe the development of teacher performance at MI Al-Kadariah Congko Kab. Bone as well as to describe the implementation of academic supervision activities at MI Al-Kadariah Conko Kab. Bone. This research was conducted at MI Al-Kadariah Conko Kab. Bones. The research time is planned from January to April 2019. This research focuses on implementation, so it is not intended to test hypotheses or experiments. Therefore, the appropriate research method to examine these problems is a qualitative method. Based on the results of the research conducted, it can be concluded that teacher performance development through the academic supervision of the madrasah principal at MI Al-Kadariah Congko is teacher performance development at MI Al-Kadariah Conko carried out through several activities that are carried out regularly and have been planned. Routine coaching includes tahsin training and English language training.